शिक्षा ते मनुक्खी संसाधन बकास - Rao, V.K.R.V. (My University, 2020)
The book emphasizes the need for human resource development for the development of any nation. It has an exhaustive analysis of the role of education and the problems faced in the development. The importance of both aspects of education and human resource development, and their interrelationship, are elaborately discussed in the said book.
Dogri translation of Education and Human Resource Development
Keywords: Dogri